Study of the Preference Value of High-Fiber Crackers: Study of the Preference Value of High Fiber Crackers - Patrisiya, Berta; Rosida, Dedin Finatsiyatull; Wicaksono, Luqman Agung (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
Crackers are a type of biscuit made from hard dough that has been fermented. They are flat, have a salty taste, have a crunchy texture, and have layers when broken. Fermentation time influences the product's appearance, aroma, and nutritional quality. The Indonesian population does not consume enough fiber, which can increase obesity rates. Dietary fiber is contained in mocaf flour, red bean flour, and rice bran. The research aims to determine the proportion of wheat flour, mocaf flour, red bean flour, and rice bran with variations in fermentation time, on the preference value of crackers. This research used a Completely Randomized Design (CRD), arranged factorially with 2 factors. Factor I is the ratio of wheat flour, mocaf flour, red bean flour, and rice bran 70:21:4.5:4.5; 70:15:7.5:7.5; and 70:9:10.5:10.5. Factor II fermentation time 20 minutes; 40 minutes; and 60 minutes. The best treatment is crackers with a ratio of 70:21:4.5:4.5 with 40 minutes of fermentation. It has a color score of 3.38 (brownish yellow), an aroma score of 3.36 (normal), a taste score of 3.40 (normal), and a texture score of 3.36 (normal).